An Overview on Gripping Force Measurement at the Micro and Nano-Scales Using Two-Fingered Microrobotic Systems. (20th March 2014) - Boudaoud, Mokrane; Regnier, Stephane
Two-fingered micromanipulation systems with an integrated force sensor are widely used in robotics to sense and control gripping forces at the micro and nano-scales. They became of primary importance for an efficient manipulation and characterization of highly deformable biomaterials and nanostructures. This paper presents a chronological overview of gripping force measurement using two-fingered micromanipulation systems. The work summarizes the major achievements in this field from the early 90s to the present, focusing in particular on the evolution of measurement technologies regarding the requirements of microrobotic applications. Measuring forces below the microNewton for the manipulation of highly deformable materials, embedding force sensors within microgrippers to increase their dexterity, and reducing the influence of noise to improve the measurement resolution are among the addressed challenges. The paper shows different examples of how these challenges have been addressed. Resolution, operating range and signal/noise ratio of gripping force sensors are reported and compared. A discussion about force measurement technologies and gripping force control is performed and future trends are highlighted.